Cascade recognition for Fe3+ and CO32− based on asymmetric squaraine dye：An application in mimicking an INHIBIT logic gate. Issue 45 (6th November 2020) - Liu, Xiaoqian; Yao, Huyin; Li, Na; Xu, Min-Min; Jiang, Chunhui; Chen, Zaixin; Wang, Yong; Shi, Haibin
Abstract: A novel fluorescent and colorimetric squaraine dye (SQ) is synthesized and its cascade recognition ability for Fe 3+ and CO3 2− is investigated by spectroscopic techniques. It has exhibited high selectivity and sensitivity for Fe 3+ over the other metal ions. The CO3 2− ion can be consequently detected by Fe 3+ displacement approach and restoring the spectral signal of SQ. The mechanism of interaction between SQ and Fe 3+ and sensing performance of CO3 2− are supported by spectroscopic changes and other analytical methods. The limit of detection (LOD) for both Fe 3+ and CO3 2− are found to be 0.14 μM and 0.17 μM, respectively. Both results are superior to the most literature reported examples. An INHIBIT logic gate can be constructed by this reversible bifunctional sensing system and the quantification of Fe 3+ in real water samples is successfully applied as well. Graphical abstract: An asymmetrical near infrared sensor was developed for consequent fluorescent recognition of Fe 3+ and CO3 2− with low detection limit and potential application in mimicking an INHIBIT logic gate. To create your abstract, type over the instructions in the template box below. Fonts or abstract dimensions should not be changed or altered. Image 1 Highlights: The highlights of this work can be summarized as following: 1. An asymmetrical squaraine based material has been developed for cascade detection of Fe 3+ and CO3 2− . 2. The material displayed reversible color and fluorescent properties. 3. The limits of detection for both ions were at nanomolar levels. 4. An INHIBIT logic gate is preliminarily constructed in the system.